2009
DOI: 10.1126/science.1175930
|View full text |Cite
|
Sign up to set email alerts
|

A Population of Compact Elliptical Galaxies Detected with the Virtual Observatory

Abstract: Science, 326, Issue 5958, pp. 1379-1382 (2009)International audienc

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
162
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(171 citation statements)
references
References 35 publications
8
162
0
1
Order By: Relevance
“…This makes them analogous to ultra-compact dwarf (UCDs) galaxies (Drinkwater et al 2003) observed in the nearby Virgo and Fornax clusters, which are known to have mass-tolight ratios consistent with the Kroupa IMF when the two-body relaxation timescales are long (Chilingarian et al 2011). UCDs are proven to be tidally stripped galactic nuclei by the recent discovery of central massive black holes (Seth et al 2014) and by their stellar population properties (Francis et al 2012) similar to much more massive tidally stripped M32-like compact elliptical galaxies (Chilingarian et al 2009;Chilingarian & Zolotukhin 2015). The only known stellar systems where central luminosity densities exceed 10 5 L pc −3 are nuclear star clusters in low and intermediate luminosity galaxies, cEs, some UCDs (Evstigneeva et al 2008) and some globular clusters.…”
Section: Discussionmentioning
confidence: 99%
“…This makes them analogous to ultra-compact dwarf (UCDs) galaxies (Drinkwater et al 2003) observed in the nearby Virgo and Fornax clusters, which are known to have mass-tolight ratios consistent with the Kroupa IMF when the two-body relaxation timescales are long (Chilingarian et al 2011). UCDs are proven to be tidally stripped galactic nuclei by the recent discovery of central massive black holes (Seth et al 2014) and by their stellar population properties (Francis et al 2012) similar to much more massive tidally stripped M32-like compact elliptical galaxies (Chilingarian et al 2009;Chilingarian & Zolotukhin 2015). The only known stellar systems where central luminosity densities exceed 10 5 L pc −3 are nuclear star clusters in low and intermediate luminosity galaxies, cEs, some UCDs (Evstigneeva et al 2008) and some globular clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Brodie et al 2011;Misgeld & Hilker 2011). This distinctively differentiates them from their low density counterparts dwarf ellipticals (dE; Chilingarian et al 2009). In fact, the vast majority of known cEs are located close to a much larger host galaxy, which plausibly has caused the threshing.…”
Section: Introductionmentioning
confidence: 99%
“…These are LEDA 3126628, LEDA 4544863, J075140.40+501102.6 (J07+50 hereafter), J160537.21+142441.2 (J16+14 hereafter), NGC 1272-cE1, NGC 2832-cE, NGC 2892 In addition, seven new objects are reported here as cEs for the first time, found through SQL searches. Automated searches for cEs in SDSS spectroscopic catalogs were first pioneered by Chilingarian et al (2009) and CZ+15, and we are developing new search techniques along similar lines (Dixon et al, in prep.). We thus use parameters previously calibrated by known cEs, imposing a redshift range (0.007< z <0.035), a stellar mass range (9.0 < logM < 13.0) and most importantly, a very restrictive size range (0.02 < R e (kpc) < 0.6).…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Kaur et al 2010), although those studies were hampered by high source density and high probability of random coincidence in 1 arcmin-scale X-ray error boxes of ASCA detections in the Galactic plane. In our study, we decided to adopt the innovative VO-powered research concept (Chilingarian et al 2009a) including the three steps: (1) search for candidate object(s) using VO technologies and infrastructure in a semi-automatic way; (2) follow-up observations; (3) interpretation of newly obtained data together with all the information available from the VO. We note that the VObased identification of an X-ray source presented hereafter was made during the tutorial for undergraduate students held at the Sternberg Astronomical Institute in May 2009 1 .…”
Section: Identification Of Ax J194939+2631mentioning
confidence: 99%